Perancangan Game Edukasi Kuis Alat Transportasi Menggunakan Aplikasi Unity - Putra Lintangasto; Yulia Ery Kurniawati (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to develop an educational game about transportations for kids on PC. It was developed as an educational medium for kids in learning transportations. The game developing method that is used is the Game Development Life Cycle (GDLC) which consists of six steps such as Initiation, Pre-Production, Production, Testing, Beta, and Release. In the Production stage, the software that is used was Unity with C# language. The result of black-box testing was all functions worked better. The result of the user experience test found that the game is difficult to be played by kids from Kindergarten to 2nd-grader and is more suitable to be played by upper than 2nd graders which has a different difficulty level than 2nd graders and below. The final result of this research is this educational game named TransportaKuis can be played by players through PC with Microsoft Windows OS.